FRI0315 First Human Dose of the Anti-C5a Receptor-Targeting, Human Monoclonal Antibody NNC0215-0384 in Patients with Rheumatoid Arthritis: A Phase 1, Randomised, Double-Blind, Single-Dose, Dose-Escalation Trial. (10th June 2014) - Wagner, F.; Lange, C.F.; Nowak, M.; Ignatenko, S.
Abstract : Background: The monoclonal antibody NNC0215-0384 blocks the complement factor 5a receptor (C5aR), mainly expressed on leukocytes, and thereby inhibits the proinflammatory signaling mediated via C5aR, which is thought to play an important role in rheumatoid arthritis (RA). 1 NNC0215-0384 is currently in clinical development as a 2nd generation compound, modified from the 1st generation compound NNC0151-0000, 2 to ensure a reduced potential of inducing Fc-mediated depletion of C5aR-expressing cells and anti-drug antibodies (ADAs). Objectives: The objective of this trial was to investigate the safety and tolerability of NNC0215-0384 in patients with RA. Methods: 36 adults with active RA (DAS28-CRP >3.2) on stable background methotrexate treatment (7.5–25 mg/week for ≥16 weeks) were randomised in a 3:1 manner to receive a single dose of NNC0215-0384 or placebo by either intravenous (i.v. [n=24]) or subcutaneous (s.c. [n=12]) administration. Six increasing i.v. dose levels (0.02, 0.08, 0.3, 1, 3 and 10 mg/kg) and three increasing s.c. dose levels (0.2, 0.8 and 4 mg/kg) were investigated. Patients were followed for 9 weeks, and the primary outcome measure was the incidence of adverse events (AEs). ADAs were also evaluated, along with pharmacokinetic (PK) and pharmacodynamic (PD) properties and efficacy measures. Clinicaltrials.gov : NCT01611688 . Results: All patients (n=36) were included in the analysis. In total, 35 AEs were reported in 22 patients (61%): i.v. group, NNC0215-0384 vs. placebo: 24 AEs in 13 patients (72%) vs. 4 AEs in 4 patients (67%); s.c. group: 7 AEs in 5 patients (56%) vs. 0 AEs. The most frequently reported AEs were nasopharyngitis and headache, with more events reported with NNC0215-0384 vs. placebo in both routes of administration. No dose-dependent increase in AEs was apparent with either route of administration. No serious AEs were observed with NNC0215-0384. ADAs were detected in low titres in 1 i.v. patient (6%) and 3 s.c. patients (33%), with no neutralising activity measured in vitro . No clinically relevant changes in vital signs, electrocardiogram or laboratory safety parameters (including leukocyte-, lymphocyte-, and neutrophil counts) were observed in any of the dose groups. NNC0215-0384 showed nonlinear PK due to target-mediated disposition. Mean C5aR occupancy, measured in peripheral blood, increased with increasing dose levels. Full mean occupancy (>90%) was maintained for 4.3 weeks (i.v. 10 mg/kg) and 1.8 weeks (s.c. 4 mg/kg), respectively. No statistically significant differences were seen between single doses of NNC0215-0384 and placebo for both routes of administration in any of the efficacy measures, including DAS28-CRP and Vectra® DA score. Conclusions: In this first-in-human trial, NNC0215-0384 was well tolerated in patients with RA at increasing doses up to 10 mg/kg i.v. and 4 mg/kg s.c. This trial provided initial information on the safety, PK and PD of NNC0215-0384. The safety data support further clinical development of the NNC0215-0384 compound for use in patients with RA. References: Jose et al. Ann Rheum Dis 1990; 49(10):747-752 Clinicaltrials.gov: NCT01223911 Disclosure of Interest: F. Wagner: None declared, C. F. Lange Shareholder of: Novo Nordisk A/S, Employee of: Novo Nordisk A/S, M. Nowak Shareholder of: Novo Nordisk A/S, Employee of: Novo Nordisk A/S, S. Ignatenko: None declared DOI: 10.1136/annrheumdis-2014-eular.2156